Protecting Child Nutritional Status in the Aftermath of a Financial Crisis: Evidence from Indonesia - John T. Giles; Elan Satriawan (Institute for the Study of Labor (IZA), 2014)
In response to concerns over the vulnerability of the young in the wake of Indonesia's 1997-1998 economic crises, the Government of Indonesia implemented a supplementary feeding program to support early childhood nutritional status. This paper exploits heterogeneity in duration of program exposure to evaluate the impact of the program on children aged 6 to 60 months. By examining differences in nutritional status of treated younger children and a placebo group of older children, the analysis finds that the program improved the nutritional status of treated children, and most significantly, led to 7 and 15 percent declines in rates of moderate and severe stunting, respectively, for children aged 12 to 24 months who were exposed to the program for at least 12 months over two years.
Keywords: I12; I18; O15; O20; O22; 330; nutritional interventions; program evaluation; poverty; financial crises; Indonesia